A Systematic Review of Lumbar Fusion Rates With and Without the Use of rhBMP-2. Issue 14 (15th July 2015) - Galimberti, Fabrizio; Lubelski, Daniel; Healy, Andrew T.; Wang, Timothy; Abdullah, Kalil G.; Nowacki, Amy S.; Benzel, Edward C.; Mroz, Thomas E.
<x xml:space="preserve">Abstract</x> Study Design. Systematic review. Objective. To evaluate literature comparing fusion rates in anterior lumbar interbody fusion (ALIF), posterior lumbar interbody/transforaminal lumbar interbody fusion (PLIF/TLIF), and posterolateral lumbar fusion (PLF) with and without recombinant human bone morphogenetic protein-2 (rhBMP-2). Summary of Background Data. rhBMP-2 is used for the FDA-approved indication of single-level ALIF with LT-Cage and off-label for PLIF/TLIF, and PLF. Due to recent controversies, it is essential to evaluate the literature for its effects on fusion rates to evaluate whether benefits outweigh potential complications. Methods. A Medline search was performed of clinical studies published between May 2000 and May 2012 comparing fusion rates after ALIF, PLIF/TLIF, and PLF surgery with versus without rhBMP-2. Only studies with a control arm were reviewed. Results. 16 studies were reviewed (1794 patients, 995 treated with rhBMP-2 and 799 without). 5 of 5 studies for PLIF/TLIF (including 301 of 301 patients), 1 of 4 for ALIF (including 279 of 589 patients), and 3 of 7 for PLF (including 272 of 904 patients) reported no significant improvement in fusion rates with rhBMP-2 compared with those without rhBMP-2 at longest follow-up investigated. Average fusion rate 24 months after surgery was 97.8% for ALIF (n = 316), 95.7% for PLIF/TLIF (n = 141), and 93.6% for PLF (n = 422) with rhBMP-2 and 88.2% (n = 228), 89.5% (n = 86), and 83.1% (n = 372) without rhBMP-2, for ALIF, PLIF/TLIF, and PLF, respectively. Odds ratio of fusion were calculated as 7.08 (95% CI: 1.54–32.7) in ALIF, 1.98 (95% CI: 0.39–10.1) in PLIF/TLIF, and 3.06 (95% CI: 1.61–5.80) in PLF with rhBMP-2 as compared with without rhBMP-2. Conclusion. Although numerous studies did not show statistically significant improvement in fusion rates with rhBMP-2 use, analysis of combined studies revealed significant improvement in fusion rate with rhBMP-2 in ALIF and PLF patients. Notably, even when pooling data from several studies, rhBMP-2 did not result in statistically significantly improved fusion rates in PLIF/TLIF. However, heterogeneity of rhBMP-2 dosing, surgical techniques, and quality of papers reviewed may limit the validity of conclusions drawn. Level of Evidence: 4